A Case Report on Palatal Dermoid with Bifid Tongue - Bhuiyan, Md Akbar Husain; Kazal, Md Ashraf ul Huq; Chowdhury, Shahanara; Chowdhury, Shafquat Haider (Journal of Chittagong Medical College Teachers’ Association, 2010)
Key words: dermoid; hard palate; bifid tongue DOI: 10.3329/jcmcta.v20i1.4938 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):58-60